Optical microscopy visualization on droplet relaxation and breakup in a LDPE modified bitumen. (5th October 2016) - Roman, C.; García-Morales, M.
Abstract: The in-service performance of polymer modified bitumens (PMBs) is strongly affected by the deformation/break-up process experienced by the dispersed phase during mixing and interfacial tension between the phases. However, not much work on this matter has been conducted. The only related approach is that proposed by Lesueur et al. (1998), who found values on the order of 10 − 5 –10 − 6  N/m by the best adjustment of the Palierne model to diblock poly(styrene-b-butadiene) (SB) modified asphalts experimental data at 120 °C. Using an optical shearing apparatus, we also found interfacial tension values on the order of 10 − 6  N/m for a low density polyethylene (LDPE) modified bitumen at 180 °C. This result is based on the direct observation on the relaxation of ellipsoidal drops and threads back to their spherical shape at rest. Further experiments on the breakup of extended filaments during retraction and the droplet deformation under oscillatory shear were also carried out. We experimentally prove that, on the timescale associated to thread retraction, the breakup of LDPE modified bitumens is governed by the so-called "end-pinching" mechanism. Moreover, when subject to oscillatory shear, the LDPE-rich droplets aligned parallel to the flow direction up to a critical shear rate value from which transverse orientation was observed. Graphical abstract: Highlights: Polymer/bitumen interfacial tension by direct visualization matches that found elsewhere by best fitting of Palierne model. The breakup during retraction of LDPE filaments on bitumen matrix is based on "end-pinching" mechanism. Elastic effects experienced by the LDPE droplets yield an alternative break-up mechanism by transverse orientation.